2009
DOI: 10.1200/jco.2008.21.4809
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Overall Survival in Patients With Metastatic Renal Cell Carcinoma Treated With Vascular Endothelial Growth Factor–Targeted Agents: Results From a Large, Multicenter Study

Abstract: This model validates components of the MSKCC model with the addition of platelet and neutrophil counts and can be incorporated into patient care and into clinical trials that use VEGF-targeted agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
1,419
6
40

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 1,861 publications
(1,549 citation statements)
references
References 24 publications
38
1,419
6
40
Order By: Relevance
“…Heng et al [76] recently expanded upon the Motzer criteria by analyzing a cohort of 645 patients with mRCC (all subtypes) treated with VEGF-targeted agents. They found that additional prognostic value for overall survival was gained from the use of higher absolute neutrophil and platelet counts (greater than the upper limit of normal), allowing for creation of three risk categories.…”
Section: Predicting Response To Systemic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Heng et al [76] recently expanded upon the Motzer criteria by analyzing a cohort of 645 patients with mRCC (all subtypes) treated with VEGF-targeted agents. They found that additional prognostic value for overall survival was gained from the use of higher absolute neutrophil and platelet counts (greater than the upper limit of normal), allowing for creation of three risk categories.…”
Section: Predicting Response To Systemic Therapymentioning
confidence: 99%
“…Several nomograms have been developed for localized and metastatic disease using factors such as histology, stage, symptoms, performance status (PS), and tumor size (Table 3) [36,[65][66][67][68][69][70][71][72][73][74][75][76]. In 2001, Yaycioglu et al [65] developed a prognostic model independent of pathological stage.…”
Section: Prognostic Schemamentioning
confidence: 99%
“…A study conducted by the MD Anderson group has also examined who will benefit from CRN and concluded that survival differences between CRN and non-CRN patients did not begin to diverge until 8.5 months [31]. There are statistical models available in predicting the OS in patients with mRCC treated with TT, and maybe, one can make use of these models while selecting patients for CRN [32]. There is no surprise that the ongoing CARMENA and EORTC SURTIME prospective trials have recruited patients with good performance status.…”
Section: Discussionmentioning
confidence: 99%
“…Ce système d'établissement du pronostic a été élaboré à l'époque des cytokines. À l'époque des traitements ciblés, Heng et ses collaborateurs ont publié un score similaire, mais pas tout à fait identique, pour la stratification en fonction du risque, score qui peut s'appliquer à tous les patients recevant un traitement de nos jours 10 .…”
Section: Traitement De Première Ligneunclassified